Entrepreneurial universities and formation features of self-learning organizations in the Russian economy - I. S. Salihova (Путеводитель предпринимателя, 2020)
The article explores the cognitive and productive potential of entrepreneurial universities as the most advancedforms of self-learning organizations in the modern knowledge economy. Characteristics of an integrated intellectual capital of this type of university, as well as identify opportunities for theirformation in modern domestic economic reality were given. In connection with this, a retrospective analysis of real forms of integration of science, education and industry in the Russian economy are considered the most promising ways of development of cognitive sector within the national organizations, including, in particular, higher education institutions. The methodological bases of the study are the provisions of systemic paradigm associated with the actualization of non-economic factors of economic dynamics. Scientific novelty of the paper is to justify the conclusion that the leading role of universities as the leading organizations in the creation of self-learning organizations, as well as to identify the specifics of their formation in modern Russian economy. Article may be used in the formation of scientific andpracticalparadigm in the creation and development of self-learning organizations in the conditions of innovative quality of our economy.